Adaptation to climate change induced water stress in major glacierized mountain regions - Aggarwal, Anubha; Frey, Holger; McDowell, Graham; Drenkhan, Fabian; Nüsser, Marcus; Racoviteanu, Adina; Hoelzle, Martin (Climate & development, 2022)
Mountains are a critical source of water. Cryospheric and hydrological changes in combination with socio-economic development are threatening downstream water security triggering the need for effective adaptation responses. Here, we present a global systematic review (83 peer-reviewed articles) that assesses different water-related stressors and the adaptation responses to manage water stress in major glaciated mountain regions. Globally, agriculture (42%), tourism (12%), hydropower (8%) and health and safety (4%) are among the main sectors affected by hydrological and cryospheric changes . A broad set of adaptation measures has already been implemented in the world’s mountain regions. We find that globally the most commonly used adaptation practices correspond to the improvement of water storage infrastructure (13%), green infrastructure (9.5%), agricultural practices (17%), water governance and policies (21%), disaster risk reduction (9.5%) and economic diversification (10%). Successful implementation of adaptation measures is limited by reduced stakeholder capacities, collaboration and financial resources, and policies and development. To overcome these limitations, funding for climate change adaptation and development programmes in mountains and trust-building measures such as shared stakeholder activities need to be strengthened. Local awareness raising of both, the adverse effects of climate change and potentially positive implications of specific adaptation measures can help to support successful adaptation.